Complex Tissue Regeneration in Mammals Is Associated With Reduced Inflammatory Cytokines and an Influx of T Cells - Gawriluk, Thomas R.; Simkin, Jennifer; Hacker, Corin K.; Kimani, John M.; Kiama, Stephen G.; Ezenwa, Vanessa O.; Seifert, Ashley W. (Frontiers in Immunology, 2020)
While mammals tend to repair injuries, other adult vertebrates like salamanders and fish regenerate damaged tissue. One prominent hypothesis offered to explain an inability to regenerate complex tissue in mammals is a bias during healing towards strong adaptive immunity and inflammatory responses. Here we directly test this hypothesis by characterizing part of the immune response during regeneration in spiny mice (A. cahirinus and A. percivali) versus fibrotic repair in Mus musculus. By directly quantifying cytokines during tissue healing, we found that fibrotic repair was associated with a greater release of pro-inflammatory cytokines (i.e., IL-6, CCL2 and CXCL1) during acute inflammation in the wound microenvironment. However, reducing inflammation via COX-2 inhibition was not sufficient to reduce fibrosis or induce a regenerative response, suggesting that inflammatory strength does not control how an injury heals. Although regeneration was associated with lower concentrations of many inflammatory markers, we measured a comparatively larger influx of T cells into regenerating ear tissue and detected a local increase in the T-cell associated cytokines IL-12 and IL-17 during the proliferative phase of regeneration. Taken together, our data demonstrate that a strong adaptive immune response is not antagonistic to regeneration and that other mechanisms likely explain the distribution of regenerative ability in vertebrates.